Television time and continuous metabolic risk in physically active adults - Healy, Genevieve; Dunstan, D.; Salmon, J.; Shaw, J.; Zimmet, P.; Owen, N. (Lippincott Williams & Wilkins, 2008)
PURPOSE: Among Australian adults who met the public health guideline for the minimum health-enhancing levels of physical activity, we examined the dose-response associations of television-viewing time with continuous metabolic risk variables. METHODS: Data were analyzed on 2031 men and 2033 women aged = 25 yr from the 1999-2000 Australian Diabetes, Obesity and Lifestyle study without clinically diagnosed diabetes or heart disease, who reported at least 2.5 h·wk of moderate- to vigorous-intensity physical activity. Waist circumference, resting blood pressure, and fasting and 2-h plasma glucose, triglycerides, and high-density-lipoprotein cholesterol (HDL-C) were measured. The cross-sectional associations of these metabolic variables with quartiles and hours per day of self-reported television-viewing time were examined separately for men and for women. Analyses were adjusted for age, education, income, smoking, diet quality, alcohol intake, parental history of diabetes, and total physical activity time, as well as menopausal status and current use of postmenopausal hormones for women. RESULTS: Significant, detrimental dose-response associations of television-viewing time were observed with waist circumference, systolic blood pressure, and 2-h plasma glucose in men and women, and with fasting plasma glucose, triglycerides, and HDL-C in women. The associations were stronger in women than in men, with significant gender interactions observed for triglycerides and HDL-C. Though waist circumference attenuated the associations, they remained statistically significant for 2-h plasma glucose in men and women, and for triglycerides and HDL-C in women. CONCLUSIONS: In a population of healthy Australian adults who met the public health guideline for physical activity, television-viewing time was positively associated with a number of metabolic risk variables. These findings support the case for a concurrent sedentary behavior and health guideline for adults, which is in addition to the public health guideline on physical activity. ©2008The American College of Sports Medicine.